Periodontitis Exacerbates and Promotes the Progression of Chronic Kidney Disease Through Oral Flora, Cytokines, and Oxidative Stress - Li, Ling; Zhang, Ya-Li; Liu, Xing-Yu; Meng, Xiang; Zhao, Rong-Quan; Ou, Lin-Lin; Li, Bao-Zhu; Xing, Tian (Frontiers in Microbiology, 2021)
Periodontitis is a type of systemic immune inflammation that is caused by the complex infection of a variety of microorganisms in the subgingival plaque and the imbalance of the microbial ecological environment in the mouth. Periodontitis and chronic kidney disease (CKD) share many risk factors, such as obesity, smoking, and age. A growing body of data supports a strong correlation between periodontitis and kidney disease. Evidence supports the role of periodontal inflammation and elevated serum inflammatory mediators in renal atherosclerosis, renal deterioration, and end-stage renal disease (ESRD) development. Periodontitis is a risk factor for kidney disease; However, to our knowledge, there are few studies detailing the possible link between periodontitis and CKD. This review summarizes the possible mechanisms underlying periodontitis and CKD. More importantly, it highlights novel and potential pathogenic factors for CKD, including bacteria, pro-inflammatory mediators and oxidative stress. However, most research on the relationship between periodontitis and systemic disease has not determined causality, and these diseases are largely linked by bidirectional associations. Future research will focus on exploring these links to contribute to new treatments for CKD.